Leitura da imagem urbana - Diretrizes para a Sustentabilidade da Orla Ribeirinha de Propriá - SE - Silva, Givaldo Barbosa da (2006)
The research has for objective to elaborate lines of direction that subsidize urban legislators and future interventions in marginal edges, being based on conceptual, theoretical beddings and methodological constituent of three methods - technician and existential - applied in the study area. To the procedures strict technician (Method of Reading of the Image of an Urban Area for its Whitewashing) of recognition of the typological morphologic characteristics of the landscape, of the problems and potentialities of the area and the discovery of the identity of the place, is added to the analysis of the experience human being and its capacity of reading of the urban image (Method of Analysis for Images and Method of Perception of the Urban Space), by means of research shows with mental interviews, maps, photographs and the interpretation of these results. The marginal edge of the city of Propriá, area of study, is not only presented while component of the urban landscape, but also for its character of ambient fragility and prominence in the economic and cultural life of the city, besides configuring an area of transition between urban and the natural one in proper, situated marginal city in the micro region of the hinterland of the San Francisco in Sergipe, where the balance of the ambient conditions is basic. It is excellent also for congregating characteristic that they make possible this marginal edge to serve as referential area for magnifying of the research in similar spaces. The general image of the area is gotten by the integration of the methods and interrelates a vision technique to another existential, main difference between the methods. The application of the first cited method allowed to distinguish as area-problem the stretch understood between the commercial center and the beach, for concentrating the biggest urban impediments, as potential area the urban emptiness located in the south extremity and the sheds of the old plants, as area of ambient interest the residential zones, as areas of ambient preservation the urban edge of the river and referential landmarks that give identity to the place. The existential methods, in which the procedures invest in deriving contents of the interpretation of the local inhabitants, make possible to conclude that the inhabitants possess an limited image of the edge, constructed from elements implanted to the long one of the time for diverse projects. Therefore, the methods applied in this research, exactly with its substantial differences, reveal complementary, favoring the analysis amplest of the ambient problematic complexity of the urban one. On the basis of the reached results, the research presents lines of direction that come to contribute with the elaboration of projects and urban plans next to the set of ideas of the sustainability, integrators and of valuation of the social and cultural aspects of each place.